Hydrodeoxygenation of vegetable oils and fatty acids over different group VIII metal catalysts for producing biofuels - Janampelli, Sagar; Darbha, Srinivas (Catalysis Surveys From Asia, 2019)
Energy security and environment protection are two important aspects of sustainable development. Biofuels are renewable and carbon neutral. They are suitable replacement for conventional fossil derived transport fuels. Their use leads to sustainable development. Among several technological options, catalytic hydrodeoxygenation of vegetable oils leading to diesel-range hydrocarbons is the most attractive approach for producing biofuels. The green diesel, thus produced, could be blended with petro-diesel or used as standalone fuel in the conventional diesel engines. Our research group has been active in developing efficient solid catalysts for hydroprocessing of vegetable oils. This account presents some of our efforts using supported group VIII metals and the importance of electronic contact between metal and support on the catalytic activity and hydrodeoxygenation selectivity in hydroprocessing of vegetable oils.
Keywords: biofuels; Catalysis over group VIII metals; Deoxygenation; Hydroprocessing; Renewable diesel